2020
DOI: 10.1186/s12877-020-01697-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired kidney function is associated with lower quality of life among community-dwelling older adults

Abstract: Background Quality of life (QoL) refers to the physical, psychological, social and medical aspects of life that are influenced by health status and function. The purpose of this study was to measure the self-perceived health status among the elderly population across Europe in different stages of Chronic Kidney Disease (CKD). Methods Our series consisted of 2255 community-dwelling older adults enrolled in the Screening for Chronic Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
(71 reference statements)
2
20
0
Order By: Relevance
“…However, we have shown that the distinction between categories G3a and G3b might be important as already in category G3a both physical HRQoL and the perceived general state of health are reduced significantly. In accordance with “the screening for CKD among older people across Europe” (SCOPE) study, we were able to prove that already in category G3a HRQoL is impaired significantly [26]. However, in contrast to the SCOPE Study which analyzed a geriatric cohort (>75 years), we could also detect the negative effect on HRQoL in a population aged 40–79 years.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, we have shown that the distinction between categories G3a and G3b might be important as already in category G3a both physical HRQoL and the perceived general state of health are reduced significantly. In accordance with “the screening for CKD among older people across Europe” (SCOPE) study, we were able to prove that already in category G3a HRQoL is impaired significantly [26]. However, in contrast to the SCOPE Study which analyzed a geriatric cohort (>75 years), we could also detect the negative effect on HRQoL in a population aged 40–79 years.…”
Section: Discussionsupporting
confidence: 66%
“…The association of the less severe stages of CKD with HRQoL remains largely unclear as the majority of studies are not population-based and have not classified renal function according to KDIGO guidelines into 5 categories (G1–G5) [3, 18-24]. Some studies could detect impairment in HRQoL in the early stages of CKD [3, 11, 18, 25, 26]. Other studies could not confirm this finding [27] or results were not significant after adjusting for confounders [11, 19, 20, 27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quality of life assessment, our participants showed no obvious deficits in vitality, social functioning, emotional role, and mental health, except for physical role function. Our analysis was mostly consistent with a recent study [ 42 ] employing the EQ-VAS, which showed impaired self-perceived quality of life in patients at CKD stages 3a, 3b, and 4 before and after adjusting for sociodemographic factors. However, the EQ-VAS is a multifactorial scale, which was scored by asking the participants to indicate their health state in a range from 0 (worst) to 100 (best).…”
Section: Discussionsupporting
confidence: 91%
“…However, few studies have investigated the association between quality of life and the early and moderate stages of CKD. We found that these studies exhibited inconsistent results: (1) a cross-sectional study of ≥60 year-old participants in North California [ 40 ] showed no relationship between eGFR and quality of life scores in physical and mental dimensions after adjustment for medical comorbidities; (2) a cross-sectional study including ≥50 year-old Irish participants [ 41 ] showed that reduced scores in quality of life are associated with eGFR by serum cystatin rather than creatinine; and (3) a recent cross-sectional study [ 42 ] enrolled 2,255 older adults in European countries and found that early CKD at stages 3a and 3b, defined by the BIS equation, is associated with lower quality of life on the EQ-Visual Analogue Scale (EQ-VAS). To our knowledge, there is a lack of relevant research on ethnic Han Chinese as well.…”
Section: Introductionmentioning
confidence: 99%